Open‐label, single‐arm, phase II study of enzastaurin in patients with follicular lymphoma. (27th March 2014) - Schwartzberg, Lee; Hermann, Robert; Flinn, Ian; Flora, Douglas; Hsi, Eric D.; Hamid, Oday; Shi, Peipei; Lin, Boris K.; Myrand, Scott P.; Nguyen, Tuan S.; Dreyling, Martin
Summary This open‐label, phase II study investigated whether enzastaurin, a protein kinase C‐beta (PKCβ) inhibitor, had activity in patients with grade 1 or 2 follicular lymphoma (FL). Adults with grade 1 or 2 FL who had no more than one prior treatment received oral enzastaurin continuously for up to 3 years. Of the 66 patients who received enzastaurin, 53 were evaluable for response. Overall response rate (ORR, primary efficacy endpoint) was 26·4% (3·8% complete response). Median (95% confidence interval) progression‐free survival, time to response, and duration of response were 18·1 (11·5–28·3), 4·9 (2·8–8·1), and 22·3 (8·8‐not applicable) months, respectively. In patients with tumour tissue available for biomarker analysis, ORRs in low versus high PKCβ2 expression groups were 41·7% and 8·3%, respectively (P = 0·041). The most common, mainly low‐grade drug‐related adverse events were fatigue (25·8%), diarrhoea (25·8%), nausea (18·2%), and chromaturia (18·2%). Four (6·1%) patients had Grade 3 toxicity and one (1·5%) patient had Grade 4 toxicity. Enzastaurin demonstrated limited clinical activity in grade 1 or 2 FL. Patients with low PKCβ2 expression in tumours had higher ORR than those with high PKCβ2 expression. Enzastaurin was well tolerated with mostly grade 1 or 2 toxicities. Further studies may be warranted in select patient populations.